A Predictive Nomogram for Red Blood Cell Transfusion in Pheochromocytoma Surgery: A Study on Improving the Preoperative Management of Pheochromocytoma - Guo, Ying; You, Lili; Hu, Huijun; Tong, Anli; Zhang, Xiaoyun; Yan, Li; Zhang, Shaoling (Frontiers in Endocrinology, 2021)
Purpose Surgery is the major treatment option for pheochromocytoma but carries potential risks, including hemorrhage and hemodynamic instability. Even with laparoscopic adrenalectomy, intraoperative blood transfusion happens from time to time, but few studies have investigated risk factors. For the first time we develop and validate a nomogram for prediction of red blood cell transfusion in pheochromocytoma surgery. Methods There were 246 patients in our center and 56 patients in Peking Union Medical College Hospital, who underwent pheochromocytoma surgery, enrolled in the study. We incorporated clinical and radiological risk factors, and presented this with a nomogram. Lasso regression model was used for feature selection. Logistic regression analysis was performed to identify the odd ratios. The performance of the nomogram was assessed with respect to its discrimination, calibration and clinical usefulness. Results Thirty-two features were reduced to five, which were phenoxybenzamine use, phenoxybenzamine treatment duration, preinduction heart rate, tumor diameter and surgical procedure. The model showed good discrimination (C-index 0.857, 95%CI 0.781-0.836) and application in the validation sets also gave good discrimination (internal validation: C-index 0.831, 95%CI 0.750-0.822; external validation: C-index 0.924, 95%CI 0.766-1.000). Calibration tested with the Hosmer-Lemeshow test yielded a good agreement between prediction and observation (training P=0.358; internal validation P=0.205; external validation P=0.395). Odd ratios of phenoxybenzamine use, phenoxybenzamine treatment duration, preinduction HR, tumor diameter and open surgery were 13.32 (95% CI 1.48-197.38, P=0.034), 1.04 (95% CI 0.99-1.08, P=0.092), 1.04 (95% CI 1.01-1.08, P=0.006), 1.03 (95% CI 1.02-1.06, P<0.001), 17.13 (95% CI 5.18-78.79, P<0.001), respectively. Decision curve analysis demonstrated the clinical usefulness of the nomogram. Conclusions This study presents a nomogram that may be used to facilitate the prediction of red blood cell transfusion in pheochromocytoma surgery and help to do the preoperative management more efficiently.